When rituals go wrong: mistakes, failure and the dynamics of ritual - Hüsken, Ute (Studies in the history of religions, 2007)
Preliminary Materials /U. Hüsken -- Introduction /Edward L. Schieffelin -- Mistakes, Procedural Errors And Incorrect Performances /U. Hüsken -- Types Of Ritual Failure And Mistakes In Ritual In Cuneiform Sources /Claus Ambos -- Failure And Mistakes In Rituals Of The European Santo Daime Church: Experiences And Subjective Theories Of The Participants /Jan Weinhold -- Failure Impossible? Handling Of Rules, Mistakes And Failure In Public Rituals Of Modern Western Societies /Burckhard Dücker -- Dealing With Deviations In The Performance Of Masonic Rituals /Jan A.M. Snoek -- Perfection And Mishaps In Vedic Rituals /Axel Michaels -- ‘All The King’s Horses And All The King’s Men’: The 2004 Red Matsyendranatha Incident In Lalitpur /Christoph Emmrich -- Preventive Measures And \'Quality Control\' /U. Hüsken -- The Sixteenth Pinda As A Hidden Insurance Against Ritual Failure /Johanna Buss -- Ensuring Ritual Competence In Ancient Greece. A Negotiable Matter: Religious Specialist /Eftychia Stavrianopoulou -- Contingencies And Emergence /U. Hüsken -- Social Consequences Of Ritual Failure: A Garhwali Case Study /Karin Polit -- When A Goddess Weeps—Ritual Failure Or Failed Performance? A Case Study From Nepal /Brigitte Merz -- Change Of View: The Ritual Side Of Serial Killings And The Conditions For Fortunate Failure /Maren Hoffmeister -- Competing Perspectives: The Discursive Production Of Ritual /U. Hüsken -- Rivalling Rituals, Challenged Identities: Accusations Of Ritual Mistakes As An Expression Of Power Struggles In Bali (Indonesia) /Brigitta Hauser-Schäublin -- Contested Ritual Property. Conflicts Over Correct Ritual Procedures In A South Indian Visnu Temple -- The Unwanted Offering. Ubiquity And Success Of Failure In A Ritual Of The Hindu Right /Christiane Brosius -- Failure Of Ritual Reinvention? Efficacious New Rituals Among Taiwan’s Aborigines Under The Impact Of Religious Conversion And Competition Between Elites /Michael Rudolph -- Ritual Dynamics And Ritual Failure -- Index /U. Hüsken.